Champions of equality - Lindop, Laurie (New York : Twenty-First Century Books, 1997)
Biographies of the following women who have made contributions toward furthering equality: Margarethe Cammermeyer, Marian Wright Edelman, Myrlie Evers-Williams, Elizabeth Glaser, Delores Huerta, Patricia Ireland, Maggie Kuhn, Wilma Mankiller, Vilma Martinez, and Eleanor Holmes Norton.
Includes bibliographical references (p. 121-122) and index.
Keywords: Women -- United States -- Biography -- Juvenile literature; Women social reformers -- United States -- Biography -- Juvenile literature; Civil rights -- United States -- Juvenile literature; Equality -- United States -- Juvenile literature; Reformers; Civil rights workers; Women -- Social conditions; Women -- Biography